Respon Morfologi Dan Biokimia Padi Lokal Rawa Merah Dan Putih Dibawah Cekaman Rendaman Secara In Vitro - Ananda Geovani Nabila Septa Pranaja; Tri Agus Siswoyo (Jurnal Ilmu Pertanian dan Perikanan, 2026)
Local swamp rice represents a valuable genetic resource with potential tolerance to flooding stress. This study aimed to analyze the morphological and biochemical responses of local red and white swamp rice varieties to submergence stress under in vitro conditions. The research employed a quantitative approach using a factorial Completely Randomized Design (CRD) consisting of two factors: rice variety and submergence treatment. Observed parameters included seed and plant morphology, total flavonoid content, total phenolic content, and soluble protein content in seeds and leaves. The results showed that local red and white swamp rice varieties exhibited better adaptation to submergence stress than several commercial rice varieties, as indicated by relatively greater plant height and root length under submerged conditions. The local red swamp rice variety exhibited the highest flavonoid and phenolic contents among all tested varieties, while submergence treatment increased flavonoid, phenolic, and soluble protein contents in most varieties. The increase in bioactive compounds and soluble proteins reflects physiological responses and defense mechanisms against oxidative stress induced by submergence. These findings suggest that local swamp rice, particularly the red swamp rice variety, has significant potential as a genetic resource for developing submergence-tolerant rice cultivars as well as a functional food source with high bioactive compound content.